Benchmarking process and its relationship with organizational performance - Hashim, Rushanim; Yusoff, Rushami Zien; Che Mat, Ruzinoor (Institut Teknologi Bandung, 2008)
Benchmarking is recognized as an essential tool for continuous improvement of quality.Nowadays, many public sector organizations have been encouraged to implement benchmarking as one way of satisfying the government’s requirement that public organizations provide best value services.This paper begins with discussion of the literature that is integrated to point out the general basis of the topic.Then, this study will address the questions of whether the factors that affecting successful benchmarking has relationship with benchmarking process as well as whether benchmarking process will lead to improvement of organizational performance. Therefore, the study had interviewed officers that involved in benchmarking project within 35 local authorities in Peninsular Malaysia. Finally, this paper also focuses on the methodology and data analysis of the study.